Nematic Liquid Crystals Embedded in Cubic Microlattices: Memory Effects and Bistable Pixels. (13th March 2013) - Serra, Francesca; Eaton, Shane Michael; Cerbino, Roberto; Buscaglia, Marco; Cerullo, Giulio; Osellame, Roberto; Bellini, Tommaso
Abstract The confinement of liquid crystals in geometries with frustrating boundary conditions gives rise to nontrivial effects such as bistability and memory. It is shown that large memory effects arise when nematic liquid crystals are embedded in cubic micrometer‐sized scaffolds made by two‐photon polymerization. The electric field alignment of the liquid crystals inside the porous medium is maintained when the applied field is above a threshold (approximately 2 V per micrometer of cell thickness). The onset of the memory is an on/off type process for each individual pore of the scaffold, and the memory typically starts emerging in one region of the structure and then propagates. The global memory effects in porous structures with controlled geometry are enhanced with respect to the case of random porous structures. This work is a proof of the "memory from topology" principle, which was previously suggested by computer simulations. These new materials can pave the way to new types of bistable displays.